Growth hormone treatment modulates active ghrelin levels in rats. (17th June 2013) - Haddad, Haytham; Mroueh, Mohamad; Faour, Wissam H.; Daher, Costantine
Abstract: Introduction : Impairments in neuroendocrine regulation of food intake and postprandial satiety are leading causes to obesity. Ghrelin peptide is a GI hormone known to increase food intake partly through induction of growth hormone. The regulation of ghrelin production is still unknown. Objective : The aim of the current study is to investigate the influence of growth hormone (Genotropin) treatment on active ghrelin levels in plasma, stomach, pancreas and kidney in rats. Material/methods : Male Sprague-Dawley rats, randomly allocated into control and three treatment groups, received daily subcutaneous injections of Genotropin at 2, 20 and 100 µg/rat/day for 5 consecutive days. Active ghrelin levels were quantified per tissue mass or tissue protein. Results : In control groups, the highest active ghrelin concentration in pmol/g tissue was found in the stomach (15.5 ± 0.21) followed by the pancreas (1.96 ± 0.066) and the kidney (1.36 ± 0.037). Genotropin treatment caused a dose dependent decrease in active ghrelin concentration in stomach, kidney and pancreas with a concomitant increase in plasma, and reaching significance at 20 and 100 µg/rat/day doses. However, the treatment caused variable effect on total protein concentrations, with a decrease in pancreas and an increase in stomach and kidney supernatants. Consequently, under such treatment, determination of active ghrelin concentration per tissue mass rather than per tissue protein is favored. Conclusions : The present study suggests a direct correlation between Genotropin treatment and active ghrelin secretion into the rat plasma via modulating its stores in stomach, kidney and pancreas.